2021
DOI: 10.3390/f12020184
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Using the Chapman–Richards and Näslund Functions to Model Height–Diameter Relationships in Hemiboreal Old-Growth Forest in Estonia

Abstract: In light of the difficulties in stand volume estimation of natural forests, we analyzed height–diameter relationships and derived a set of height estimation equations for volume estimation for naturally developing forest ecosystems, using the Järvselja old-growth and the Laeva commercial forest in Estonia as a case study. This contribution presents an approach to model individual tree height–diameter relationships for Scots pine, common aspen, silver and downy birch, Norway spruce, black alder, gray alder, lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The relationship between H and D has been described using a number of functions. In previous studies, the Chapman-Richards model has been shown to be highly flexible and exhibits satisfactory performance for fitting statistics; this model is one of the most widely used functions for developing H-D models [17,[49][50][51][52]. Therefore, the Chapman-Richards function is used in this study as the form of the BM for Mongolian pine.…”
Section: Basic and Generalized Modelmentioning
confidence: 99%
“…The relationship between H and D has been described using a number of functions. In previous studies, the Chapman-Richards model has been shown to be highly flexible and exhibits satisfactory performance for fitting statistics; this model is one of the most widely used functions for developing H-D models [17,[49][50][51][52]. Therefore, the Chapman-Richards function is used in this study as the form of the BM for Mongolian pine.…”
Section: Basic and Generalized Modelmentioning
confidence: 99%
“…The DBH of each tree was measured at 1.2 m. The tree height was obtained by measuring D r a f t approximately 30 trees selected based on diameter class. Unmeasured tree height was estimated using Näslund equation (Nigul et al 2021). In field measurements, we recorded whether trees were dead or alive.…”
Section: -1 Data Collectionmentioning
confidence: 99%